Arboviral diseases in the Western Brazilian Amazon: a perspective and analysis from a tertiary health & research center in Manaus, State of Amazonas - Maria Paula Gomes Mourão; Michele de Souza Bastos; Regina Maria Pinto de Figueiredo; João Bosco de Lima Gimaque; Valquíria do Carmo Rodrigues Alves; Maria das Graças Gomes Saraiva; Mário Luis Garcia Figueiredo; Rajendranath Ramasawmy; Maurício Lacerda Nogueira; Luiz Tadeu Moraes Figueiredo (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
The Fundação de Medicina Tropical Dr. Heitor Vieira Dourado (FMT-HVD), located in Manaus, the capital of the State of Amazonas (Western Brazilian Amazon), is a pioneering institution in this region regarding the syndromic surveillance of acute febrile illness, including arboviral infections. Based on the data from patients at the FMT-HVD, we have detected recurrent outbreaks in Manaus by the four dengue serotypes in the past 15 years, with increasing severity of the disease. This endemicity has culminated in the simultaneous circulation of all four serotypes in 2011, the first time this has been reported in Brazil. Between 1996 and 2009, 42 cases of yellow fever (YF) were registered in the State of Amazonas, and 71.4% (30/42) were fatal. Since 2010, no cases have been reported. Because the introduction of the yellow fever virus into a large city such as Manaus, which is widely infested by Aedes mosquitoes, may pose a real risk of a yellow fever outbreak, efforts to maintain an appropriate immunization policy for the populace are critical. Manaus has also suffered silent outbreaks of Mayaro and Oropouche fevers lately, most of which were misdiagnosed as dengue fever. The tropical conditions of the State of Amazonas favor the existence of other arboviruses capable of producing human disease. Under this real threat, represented by at least 4 arboviruses producing human infections in Manaus and in other neighboring countries, it is important to develop an efficient public health surveillance strategy, including laboratories that are able to make proper diagnoses of arboviruses.